Saved from a life of vice and crime : reformatory and industrial schools for girls, c.1854-c.1901 - Cale, M (1993)
Reformatory and industrial schools were semi-penal Victorian institutions designed, firstly, to reclaim juveniles from a nascent criminal career and, secondly, to prevent neglected children from slipping into criminality. Most existing studies of these schools have been principally concerned with the campaigning philanthropists, such as Mary Carpenter, central government activity, and institutions for boys. This thesis utilises hitherto unused archival sources relating to individual institutions for girls in order to look at various aspects of reformatory life from the perspective of those by whom it was daily experienced. In addition to a consideration of the lives of the inmates, there are discussions of the motivations of the voluntary managers and the pay and conditions of the staff. A data base of industrial school cases from the Children's Society is analysed, in conjunction with other committal records, to ascertain which children were most likely to find themselves incarcerated. The importance of the respectability of a child's mother is particularly highlighted. The role of sexuality is discussed, in relation to attitudes towards girl delinquents, the selection of girls for committal, and the prevention of immorality within the schools. The internal disciplinary regime is considered in two chapters, the first concentrating on the forms of punishment and reward common throughout the reformatory system; and the second on the kinds of outburst and disturbance which contemporaries labelled hysterical, but which could be interpreted as calculated resistance to authority. Special attention is paid to the issue of corporal punishment. The socialising education in feminine, domestic skills which was provided in these institutions is the subject of a further chapter. Finally, the destinations of the 'reformed' girls on release is analysed, again using the Children's Society cases. The little which is known of their adult lives and various tokens of 'success' or 'failure' are delineated in an attempt to assess whether the schools accomplished their numerous aims.